Role of Women in Good Governance - Showkat Ahmad Dar; Aadil Ahmad Shairgojri (Syntax Corporation Indonesia, 2022)
The purpose of this study is to describe and analyse the significance of gender mainstreaming in good governance for the overall growth of the nation, with a particular emphasis on how gender engagement in decision making through consensus building and representation directly leads to women's empowerment. Qualitative study employed descriptive and analytic methods to achieve a conclusion by extensively utilising a thematic analytical tool. The concept of